Epilepsy genetics: clinical impacts and biological insights. Issue 1 (January 2020) - Ellis, Colin A; Petrovski, Slavé; Berkovic, Samuel F
Summary: Genomics now has an increasingly important role in neurology clinics. Regarding the epilepsies, innovations centred around technology, analytics, and collaboration have led to remarkable progress in gene discovery and have revealed the diverse array of genetic mechanisms and neurobiological pathways that contribute to these disorders. The new genomic era can present a challenge to clinicians, who now find themselves asked to interpret and apply genetic data to their daily management of patients with epilepsy. Navigation of this new era will require genetic literacy and familiarity with research advances in epilepsy genetics. Genetic epilepsy diagnoses now directly affect clinical care, and their importance will only increase as new targeted treatments continue to emerge. At the same time, new genetic insights challenge us to move from a deterministic view of genetic changes to a more nuanced appreciation of genetic risk within complex neurobiological systems that give rise to epilepsy.